2021
DOI: 10.1038/s41598-021-92560-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between domain-specific physical activity and diabetes in Korean adults

Abstract: This study aimed to investigate the association between domain-specific physical activity (PA) and diabetes in Korean adults. We analyzed 26,653 men and women (aged > 18 years) from the Korea National Health and Nutrition Examination Survey (2014–2018). PA was measured using a validated Global PA Questionnaire. Multivariable logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) after adjustment for various confounders. Transport PA accounted for the majority of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…However, the link between PA and T2DM may not always be plausible, and it may be influenced by gender and the kind of PA. According to a study in Korean adults, wsorking PA was not associated with T2DM risk, whereas transport PA was solely linked to T2DM in males ( 9 ). One previous MR study reported that objectively measured average or vigorous physical activity and SB are not associated with the risk of T2DM ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the link between PA and T2DM may not always be plausible, and it may be influenced by gender and the kind of PA. According to a study in Korean adults, wsorking PA was not associated with T2DM risk, whereas transport PA was solely linked to T2DM in males ( 9 ). One previous MR study reported that objectively measured average or vigorous physical activity and SB are not associated with the risk of T2DM ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the link between PA and T2DM may not always be plausible, and it may be influenced by gender and the kind of PA. According to a study in Korean adults, working PA was not associated with T2DM risk, whereas transport PA was solely linked to T2DM in males ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity domains (i.e., leisure, work, and transportation) may have varying associations with CHD. Leisure activity has an inverse linear association with CVD risk factors and mortality 22 , 23 . Associations of other physical activity domains with cardiovascular health remain less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological evidence points to a stronger protective association for leisure-time activity and nonutilitarian transport than other domains of activity in terms of all-cause mortality 29 and chronic disease incident risk. [30][31][32] This suggests that leisure-time PA, and possibly active transport, should be measured specifically in surveillance systems. Furthermore, occupational activity sometimes shows a paradoxical relationship with health outcomes, 33 and the independent benefits of domestic activity are not known.…”
Section: Discussionmentioning
confidence: 99%